1994
DOI: 10.1289/ehp.94102s105
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-derived species: their relation to human disease and environmental stress.

Abstract: Free radicals and other reactive oxygen species (ROS) are constantly formed in the human body, often for useful metabolic purposes. Antioxidant defenses protect against them, but these defenses are not completely adequate, and systems that repair damage by ROS are also necessary. Mild oxidative stress often induces antioxidant defense enzymes, but severe stress can cause oxidative damage to lipids, proteins, and DNA within cells, leading to such events as DNA strand breakage and disruption of calcium ion metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
276
0
20

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(303 citation statements)
references
References 81 publications
2
276
0
20
Order By: Relevance
“…Both radicals show similar bi-phase kinetic reactions with many antioxidants. Hydrogen peroxide itself is not very reactive, but it would provide highly reactive species OH -through Fenton reaction (Halliwell and Cross 1994). Earlier reports suggested that H 2 O 2 could induce DNA breakage in the intact cell and purified DNA (Imlay and Linn 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Both radicals show similar bi-phase kinetic reactions with many antioxidants. Hydrogen peroxide itself is not very reactive, but it would provide highly reactive species OH -through Fenton reaction (Halliwell and Cross 1994). Earlier reports suggested that H 2 O 2 could induce DNA breakage in the intact cell and purified DNA (Imlay and Linn 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The latter especially applies to the model of H # O # -mediated cell injury which has been studied extensively for several years [19][20][21] and in which protection by Bcl-2 has been described too, including inhibition of H # O # -induced rise in cytosolic Ca# + and of H # O # -induced depletion of the endoplasmic-reticulum Ca# + pool [22][23][24]. We therefore set out to test the hypothesis that in Bcl-2-transfected Rat-1 fibroblasts treated with H # O # the increase in cytosolic free Ca# + is secondary to the oxidation of cellular glutathione and that Bcl-2 influences intracellular Ca# + fluxes only indirectly by altering cellular glutathione metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, LPOs have been correlated with a variety of pathologies and cellular dysfunction (Asano et al, 1989;Rao, 1990;Halliwell and Cross, 1994;Girotti, 1998;Spiteller, 2001). It should be noted that, whereas histological analysis only samples a very small portion of the total retina, the LPO assay provides a global measure of the entire retinal LPO content.…”
mentioning
confidence: 99%